The Effect of STEM-Based Small-Scale Chemistry (SSC) Learning Assisted by SOCKit on Systems Thinking Skills - Rahmawati, Layla Nur; Ariani, Sri Retno Dwi; Shidiq, Ari Syahidul (PAEDAGOGIA, 2000)
Learning chemistry in the 21st century requires students to have systems thinking skills to understand the relationship between chemistry concepts and energy, environmental, and sustainability issues. These skills are important because they help students understand cause-and-effect relationships, integrate cross-disciplinary concepts, and make informed decisions in the face of global challenges. However, students' system thinking skills still need to be improved, especially in reaction level material related to the context of the alcohol industry and the use of renewable energy. This study aims to analyze the influence of STEM-SSC (Small Scale Chemistry) learning fostered by SOCKit media on students' system thinking ability. The method used was a quasi experiment with a pretest-posttest control group design  involving an experimental class and a control class at SMA Negeri 3 Sragen. The research instrument is a validated system thinking skills test. Data analysis was carried out using N-gain test and statistical test. The results showed that the average posttest score of students' systems thinking skills in the experimental class (79.53) was higher than that of the control class (49.58). The average N-gain test results of the experimental class (0.66) were higher than those of the control class (0.30). The results of the Wilcoxon test showed a significant improvement in the group (p < 0.001), while the results of the Mann-Whitney test showed a significant difference between the experimental class and the control class (p < 0.001). Thus, SOCKit-assisted STEM-SSC learning is used effectively to develop students' systems thinking skills,